Prominent Indonesian Chinese biographical sketches - Suryadinata, Leo (Institute of Southeast Asian Studies, 2015)
Indonesia is the largest country in Southeast Asia where there is a significant number of ethnic Chinese, many of whom have played an important role. This book presents biographical sketches of about 530 prominent Indonesian Chinese, including businessmen, community leaders, politicians, religious leaders, artists, sportsmen/sportswomen, writers, journalists, academics, physicians, educators, and scientists. First published in 1972, it was revised and developed into the present format in 1978, and has since been revised several times. This is the fourth and most up-to-date version.